IMPOLITENESS STRATEGIES USED BY MALE AND FEMALE HATERS OF HABIB RIZIEQ AND FELIX SIAUW FOUND IN INSTAGRAM COMMENTS - Vira Apriliyani; Hamzah Hamzah; Delvi Wahyuni (English Language and Literature, 2019)
Abstract             This study aims to find out the types of impoliteness strategies that used by male and female haters of Habib Rizieq and Felix Siauw found in instagram comments. Moreover, researcher also finds the differencess of impoliteness strategies that used by male and female haters. This study is descriptive research. The data is taken from the comments contained about Habib Rizieq and Felix Siauw in instagram. They are @Maklameturah, @FelixSiauw, @Habib Rizieq, @Rakyatbersuara11, and @Detikcom. The researcher login to instagrams accounts, then searching instagram accounts meantioned before. The result shows that the male and female haters only use four of five impoliteness strategies. The strategies are bald on record, positive impoliteness, negative impoliteness, and sarcasm or mock politeness. From total 100 comments by male haters there were found 253 impoliteness strategies and it sub strategies. However, from total 100 comments by female haters there were found 231 impoliteness strategies and it sub strategies. The higher impoliteness strategies that used by male and female haters is sarcasm or mock politeness. Researcher finds the differences between male and female haters but it is not significance. The differences between male and female haters were 10%.  Key words: impoliteness strategies, comments, instagram.